2020
DOI: 10.12659/msm.919105
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Changes of White Matter Microstructures in Tobacco Addicts Based on Diffusion Tensor Imaging

Abstract: Departmental sources Background: The tract-based spatial statistics (TBSS) method was used to investigate the changes of white matter microstructure in tobacco addicts, and to analyze its correlation with smoking index, smoking years, and daily smoking amount. Material/Methods: Routine magnetic resonance imaging (excluding intracranial lesions) and diffusion tensor imaging (DTI) sequence scanning were performed in 156 nicotine addicts (nicotine dependence group) and 81 non-nicotine addicts (control group) recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The study revealed significant, system-specific effects of perinatal exposure to secondhand smoke on sensory brain structures later in life [ 14 ]. Similarly, in a magnetic resonance imaging study, nicotine potential of destruction to white matter and neurons was confirmed [ 68 ]. Moreover, nicotine deprivation in smokers was associated, in an MRI study, with lower brain activity in its areas responsible for attention contrary to areas involved with craving, which showed lower activity when nicotine was present [ 69 ].…”
Section: Resultsmentioning
confidence: 85%
“…The study revealed significant, system-specific effects of perinatal exposure to secondhand smoke on sensory brain structures later in life [ 14 ]. Similarly, in a magnetic resonance imaging study, nicotine potential of destruction to white matter and neurons was confirmed [ 68 ]. Moreover, nicotine deprivation in smokers was associated, in an MRI study, with lower brain activity in its areas responsible for attention contrary to areas involved with craving, which showed lower activity when nicotine was present [ 69 ].…”
Section: Resultsmentioning
confidence: 85%
“…Our study is the first to integrate white matter microstructural integrity into the multiple levels of impairment that SUD patients exhibit in Low FA values typically reflect low coherence of the linear microstructure of white matter tracts. 42 As presumed outcomes of the toxic effect of substance use, studies demonstrated that FA values decrease with heavy 43 or long-term drinking, 44 continued smoking 45 and cannabis use 46 generally with lower scores being linked to poorer clinical outcomes. In our study, lower FA values in clusters encompassing the callosal genu and body and the bilateral anterior corona radiata were linked to poorer mean inhibition performance assessed via mobile Stroop testing in the SUD sample.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, we included-apart from age, sex, ADHD and ICV-MDMA and nicotine in all models, as it has been shown that MDMA can alter GM and WM integrity, 88 whereas nicotine alters WM microstructure. 89,90 These models are likely to illustrate WM alterations by the particular substances compared with HC. Yet, as HC did not consume cocaine or levamisole, we could not enter all three variables (alcohol, cocaine and levamisole) in one statistical model to assess the strongest impact on WM integrity by a particular substance by this comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we adjusted for age, sex, ADHD, nicotine, MDMA, ICV, alcohol and cocaine use. Model 3: Testing for the influence of alcohol on WM integrity. Here, we adjusted for age, sex, ADHD, nicotine, MDMA, ICV, levamisole and cocaine use. Consistently, we included—apart from age, sex, ADHD and ICV—MDMA and nicotine in all models, as it has been shown that MDMA can alter GM and WM integrity, 88 whereas nicotine alters WM microstructure 89,90 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation